The Postmodern Non-city in Miquel de Palol’s "El Jardí del Set Crepuscles" - Giordano, Chiara (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2016)
El Jardí del Set Crepuscles –the first novel of Catalan writer and architect Miquel de Palol– gives us the opportunity to reflect on the metamorphosis of western cities in the early seventies of the last century. According to authors such as Henri Lefebvre, David Harvey, Giandomenico Amendola or Edward Soja, the emergence of the postmodern city during the transition to the post-Fordist regime of accumulation occurs accompanied by a weakening of the public sphere. The objective of this paper is to illustrate the narrative and rhetorical strategies used by Miquel de Palol to represent and analyze this transformation.